The Anonymous Catechism of 1605: Slavic Loanwords and Hybrids - Smetonienė, Anželika (Lietuvių kalba, 2021)
The Anonymous Catechism of 1605 (hereinafter - AC) is one of the first catechisms in the Lithuanian language in GDL. However, it has been under-researched so far. In 1890 this catechism was published by J. Bystroń with comments. Z. Zinkevičius and A. Judžentis have conducted some research on the AC and S. Temčinas has also discussed it in his research works. However, in more recent works this catechism has not received sufficient focus and, even more, its loan lexicon has not been attentively investigated. Namely the loan lexicon, i.e., Slavic loanwords and hybrids that derive from them, is the focus of this article. Slavic loanwords and hybrids were selected from the AC and the dictionaries of Slavic languages were analysed searching for possible sources of loanwords. Following various criteria (availability of source, morphological, phonetic criteria), Slavic loanwords were grouped into Slavic borrowings of unclear origin, loanwords from the East Slavic languages (Old Russian or Ruthenian languages) and Polish loanwords. Fifty six Slavic loanwords were identified in the AC: 52 % out of them are of unclear origin, i.e., their possible sources were identified in the East Slavic and Polish languages and etymological dictionaries provide for different sources of their origin. 38 % of Slavic loanwords were borrowed into the Lithuanian language from the East Slavic language – the Polish language does not possess possible equivalents of Slavic loanwords or the meaning of Polish word does not coincide with semantics of a loanword, phonetics of borrowing also indicates such origin. Polish loanwords comprise only 10 % of all the loanwords in the AC.